Optimizing Logistics: Developing An Efficient Tracking and Delivery System for Automotive Spare Parts - Hiuredhy, Davin Kurnia; Christanto, Henoch Juli; Dewi, Christine; Sutresno, Stephen Aprius (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the automotive spare parts industry, efficient supply chain management is the backbone of operational success. Amidst this complex ecosystem, companies face challenges in delivering fast, reliable, and competitive services, accommodating a constantly evolving consumer base with discerning preferences and rising expectations. This article aims to identify challenges in developing tracking and delivery scheduling applications for the automotive spare parts industry and improve system performance by introducing effective solutions. The research adopts a system development approach using the Waterfall method to produce a responsive and user-friendly web application, followed by functional testing using Black Box and evaluation using the System Usability Scale (SUS). Development of the tracking and delivery scheduling application using the Waterfall method resulted in a reliable and responsive application, with all system functionalities running smoothly. SUS testing indicated that the application has a good level of usability, with an average score of 77.5 out of 100. This study successfully provides relevant and efficient technological solutions to overcome operational barriers in the automotive spare parts industry, with the potential to enhance customer satisfaction and solidify the company's position as a pioneer in the automotive aftermarket sector. However, further improvements in application usability can be achieved through future iterations guided by user feedback and additional usability testing.